Pengaruh Inflasi dan Nilai Tukar Kurs US Dollar terhadap Suku Bunga (BI Rate) di Indonesia, 2006-2011 - Irma Suryani; Nurul Anwar (EKO-REGIONAL, 2012)
The purpose of this article is to analysis influence inflation and exchange rate US Dollar to interest rate (BI Rate). “The Taylor Rule”, according to which the nominal interest rate should respond more than one for one to inflation.Independent in this article are inflation and exhange rate of US Dollar. Dependent is interest rate (BI Rate). Technique sampling used with listed in Indonesian Finacial Statistic of Bank Indonesia. Sample of research are consist of 24 sample. Data technique analysis used in this article is double linear regression analysis and assumption classic test.The result of this article indicates that by parsial analysis inflation does a significant positive effect to interest rate (BI Rate). Exchange rate does not a significant effect to interest rate (BI Rate). Keywords: Taylor Rule, interest rate (BI Rate), inflation, and exchange rate US Dollar